2017
DOI: 10.1055/s-0037-1604240
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma for the Aesthetic Surgeon

Abstract: Platelet-rich plasma (PRP) is an autogenously harvested blood plasma containing concentrated levels of platelets and growth factors. PRP has been identified as a promising treatment for enhancing wound healing and has been used for decades in multiple medical specialties including cardiac surgery, oral surgery, ophthalmology, and orthopedic surgery. Growing evidence for multiple aesthetic surgery applications has recently been developed, particularly for hair restoration and skin rejuvenation. The goal of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The composition of PRP consists primarily of a high concentration of platelets and growth factors but can also include white blood cells and other vasoactive and chemotactic agents 29 . PRP releases growth factors that expedite wound healing via cell proliferation, matrix formation, osteoid production, connective tissue healing, angiogenesis, and collagen synthesis 30,31 . PRP injections have been shown to have a broad range of applications in tissue sealing, stabilization, scar maturation, osteogenesis, and alopecia across various surgical specialties from orthopedics to cosmetic surgery with virtually no adverse side effects 32–34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of PRP consists primarily of a high concentration of platelets and growth factors but can also include white blood cells and other vasoactive and chemotactic agents 29 . PRP releases growth factors that expedite wound healing via cell proliferation, matrix formation, osteoid production, connective tissue healing, angiogenesis, and collagen synthesis 30,31 . PRP injections have been shown to have a broad range of applications in tissue sealing, stabilization, scar maturation, osteogenesis, and alopecia across various surgical specialties from orthopedics to cosmetic surgery with virtually no adverse side effects 32–34 .…”
Section: Discussionmentioning
confidence: 99%
“…29 PRP releases growth factors that expedite wound healing via cell proliferation, matrix formation, osteoid production, connective tissue healing, angiogenesis, and collagen synthesis. 30,31 PRP injections have been shown to have a broad range of applications in tissue sealing, stabilization, scar maturation, osteogenesis, and alopecia across various surgical specialties from orthopedics to cosmetic surgery with virtually no adverse side effects. [32][33][34] In vivo studies revealed the effect of PRP in vocal fold healing in rabbit models following acute vocal fold injury.…”
Section: Discussionmentioning
confidence: 99%
“…For example, autologous platelet-rich plasma (PRP) can be injected preoperatively to improve blood flow in the scarred areas and intraoperatively to reduce damage to the transplanted hair follicles, accelerate wound healing, and activate dormant follicles. [10][11][12][13][14] Preoperative fat grafting or temporal fascial flap transplantation can also be performed to increase the thickness of the local subcutaneous fat layer, improve the local microenvironment, soften the scar tissue, and enhance blood supply. 15 Moreover, adipose-derived stem cells (ADSCs) from fat grafts have a positive effect on the reconstruction of newly formed hair follicles.…”
Section: Ta B L Ementioning
confidence: 99%
“…Among all these applications, PRP has also been used in aesthetic applications, such as skin rejuvenation procedures [ 214 , 215 , 216 ] and hair restoration, showing better outcomes than conventional treatments [ 216 , 217 ].…”
Section: Other Clinical Applicationsmentioning
confidence: 99%